NIR-reflecting properties of new paints for energy-efficient buildings. (June 2015) - Cozza, E.S.; Alloisio, M.; Comite, A.; Di Tanna, G.; Vicini, S.
Graphical abstract: Highlights: Smart paints for cool building facades have been produced. Infrared-reflecting pigments achieve great improvement of Total Solar Reflectance. Higher is the TSR of the paint, lower is the overheating of the irradiated paint. Cool paints provide concrete solutions for energy efficiency in buildings. Abstract: The main idea of the research is to formulate exterior building paints as smart coatings with high IR-reflectance to decrease the use of energy for cooling buildings. A vantage coming from this strategy is to broaden the range of colors of the urban aesthetic request to the dark ones, overtaking the current white-cool solutions. Starting from the evidence that black color is the most critical case for the light absorption, the study was focused on black pigments, considering its use for realizing both black paints and different shades of grey paints. Five different black colorants produced in laboratory have been mixed with commercial paints and have been compared to the standard black colorant usually used for building paints. The calculated Total Solar Reflectance (TSR) values prove the increase of the solar reflectance from 5%, in case of standard black, to values over 30% for some reflective blacks. Likewise, reflective grey offers higher TSR values than standard grey at same light shade; while, at same TSR value, reflective grey has darker color shade than standard grey. Thermal measurements and thermographic images confirm that, when TSR is higher, the surface temperature on the back of painted support is lower.